2021
DOI: 10.2174/2666958702101010038
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Naturally Occurring Antiviral Molecules for SARS-CoV-2 Mitigation

Abstract: Aim: This study aimed to virtually screen the naturally occurring antiviral molecules for SARS-CoV-2 mitigation based on multiple molecular targets using docking and molecular dynamics simulations. Background: The coronavirus catastrophe (COVID-19) caused by a novel strain of coronavirus (SARS-CoV-2) has turned the world upside down at an unprecedented level and has been declared a pandemic by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Therefore, for infectious diseases in particular, people need to go back to medicinal plants, which are a huge and all-natural drug store [ 36 ]. This study put a special emphasis on finding inhibitors against the main protease (M pro ), as it is considered an ideal target for the treatment of COVID-19 [ 37 , 38 , 39 , 40 , 41 , 42 ]. The blind molecular docking approach was performed utilizing the elucidated compounds extracted in water at room temperature from Saussurea costus .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for infectious diseases in particular, people need to go back to medicinal plants, which are a huge and all-natural drug store [ 36 ]. This study put a special emphasis on finding inhibitors against the main protease (M pro ), as it is considered an ideal target for the treatment of COVID-19 [ 37 , 38 , 39 , 40 , 41 , 42 ]. The blind molecular docking approach was performed utilizing the elucidated compounds extracted in water at room temperature from Saussurea costus .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its anti-inflammatory effects, in vitro studies have shown that ginkgetin can be used in the treatment of inflammation-related diseases such as airway inflammation [ 56 ] and diabetic nephropathy [ 57 ]. It may also be useful as an antiviral [ 32 ], antibacterial [ 30 ] and antiparasitic [ 58 ] agent and has gained attention in recent years as a target for the treatment of SARS-CoV-2 infection [ 59 , 60 , 61 ].…”
Section: Ginkgetinmentioning
confidence: 99%
“…Flavonoids are widely recognized as a molecule with good antioxidant activity and beneficial effects in the treatment of neurological disorders [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ,…”
Section: Ginkgetin For the Treatment Of Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found these papers for the SARS-COV-2 spike protein with MD simulations for 150-200 ns. [43][44][45][46] Finally, the MD run was conducted for 150 ns with all the constraints released.…”
Section: Molecular Dynamics (Md) Simulationsmentioning
confidence: 99%